Developing pronunciation through creative drama. Issue 2 (4th March 2021) - Korkut, Perihan; Çelik, Özkan
ABSTRACT: Traditionally, pronunciation is taught through recognition- or repetition-based mechanical drills. Upon the arrival of the communicative approach, pronunciation has been neglected in the ELT classroom because these types of activities are considered uncommunicative and form-focused. The teachers and coursebooks, however, have failed to replace these activities with communicative ones. The need to find other ways of teaching pronunciation whereby students will be engaged with the language in meaningful ways integrated with other skills is highlighted. In this study, by means of dramatic situations, the students are provided with a meaningful context which gives them a communicative purpose for giving constant priority to accuracy. By this means, they engage in the communicative activity and still get the benefit from repetition and focus-on-form while learning pronunciation. The researchers developed 18 hours of creative drama sessions directed towards a variety of segmental and suprasegmental level problems which Turkish learners of English can encounter. These sessions were then held with a group of 12 volunteer students from the ELT department during a 6-day period. The effect of the creative drama sessions was measured via a read-aloud task which was given to the participants as pre- and post-test. All participant students did better in the post-test. The results showed that the students' pronunciation improved more at the suprasegmental level.